Axillary dissection in patients with preoperative positive nodal cytology: Genuine need or overtreatment?. Issue 2 (25th August 2019) - Liberale, Viola; Rosso, Roberta; Arisio, Riccardo; D'Alonzo, Marta; Villasco, Andrea; Fuso, Luca; De Sanctis, Corrado; Modaffari, Paola; Biglia, Nicoletta
Abstract: Recent studies demonstrated the possibility to avoid axillary dissection (ALND) in selected patients with one or two metastatic nodes. Otherwise, patients with positive nodal ultrasound‐guided fine‐needle aspiration cytology (US‐FNAC) currently undergo ALDN. The aim of this study is to quantify the nodal burden in patients with positive US‐FNAC treated with ALND and to evaluate if clinical or pathological characteristics associated with low nodal involvement can be identified. This is a multicentric retrospective study involving 297 patients who underwent ALND because of a positive preoperative US‐FNAC. A total of 157 patients showed bulky axillary lymph nodes at diagnosis, and 70% of them had three or more metastatic nodes. One hundred and forty patients had a clinically negative axilla and in 50% of them, 4 or more metastatic nodes were found with axillary dissection. Overall, the median number of metastatic nodes was 5. Favorable pathological characteristics of tumors were found in patients with only one or two metastatic nodes: smaller primary tumor, a lower proportion of grade 3, invasive lobular carcinomas and a higher proportion of low‐Ki67 tumors. In the group of patients with clinically negative axilla and potentially meeting ACOSOG Z0011 criteria, 22 (31%) showed less than three metastatic axillary nodes. A preoperative positive axillary FNAC is associated with a metastatic nodal burden significantly higher than in patients with positive sentinel lymph node biopsy (SLNB). Nevertheless, about 30% of patients with cN0 axilla, positive axillary FNAC performed because of suspicious nodes on imaging, T1‐2 primary tumor and breast‐conserving surgery showed less than three metastatic axillary nodes, thus meeting ACOSOG Z0011 trial's criteria and therefore would be eligible for skipping ALND according to current guidelines.